Differentiating malignant from benign thyroid nodules with indeterminate cytology by 99mTc-MIBI scan: a new quantitative method for improving diagnostic accuracy - A. Campennì (Nature Portfolio, 2017)
Abstract Quantitative 99mTc-MIBI thyroid scintigraphy is a useful tool in differentiating malignant from benign thyroid nodules with indeterminate cytology. The aim of our report is to compare the diagnostic performance of different quantitative methods. We prospectively evaluated 20 patients affected by a thyroid nodule with a cytological diagnosis of class III or IV according to the Bethesda system. Planar images of the thyroid were acquired 10 and 60 minutes after 99mTc-MIBI administration and two different quantitative methods applied (i.e. wash-out index, WOind; retention index, R.I.). All patients underwent lobectomy or thyroidectomy and final histological findings were matched with MIBI results obtained with both quantitative methods. Four out of 20 patients had a final histological result of differentiated thyroid cancer, while benign findings were found in the remaining cases. Overall sensitivity, specificity, accuracy, PPV and NPV were 100% in all for the WOind and 100%, 57.1%, 62.5%, 25% for the R.I., respectively. In conclusion 99mTc-semiquantitative MIBI thyroid scintigraphy with WOind calculation is highly accurate in differential diagnosis of nodules with indeterminate cytology reading.